Fecal microbiota characterization of an Italian local horse breed - Carrillo Heredero, Alicia Maria; Sabbioni, Alberto; Asti, Vittoria; Ablondi, Michela; Summer, Andrea; Bertini, Simone (Frontiers in Veterinary Science, 2024)
The Bardigiano horse is a traditional native Italian breed with a rich history and peculiar characteristics. Local breeds are proven to have unique genetic traits developed over generations to adapt to defined geographical regions and/or conditions. The specific microbial communities that coexist within these animals are unraveled by studying their microbiota, which permits a further step in the characterization of local heritage. This work aimed to characterize Bardigiano horse fecal microbiota composition. The data obtained were then compared with published data of a mix of athlete breeds to evaluate potential differences among local and specialized breeds. The study involved 11 Bardigiano mares between 3 and 4 years of age, from which stool was sampled for the study. Samples were processed for 16S rRNA sequencing. Data obtained were analyzed and plotted using R, RStudio, and FastTree software. The samples analyzed were similar to what literature has reported on horses of other breeds and attitudes at higher taxonomic levels (from phylum to genera). While at lower taxonomic levels, the difference was more marked highlighting specific families found in the Bardigiano breed only. Weight, province of origin, and breeding sites significantly affected microbiota composition (p-value ≤ 0.02, p-value ≤ 0.04, and p-value ≤ 0.05, respectively). The comparison with athlete breed showed a significant difference confirming that animal and environmental factors are crucial in determining fecal microbiota composition (p-value < 0.001). Understanding the microbiota composition in local breeds like the Bardigiano horse is crucial for preserving biodiversity, managing animal health, and promoting sustainable farming practices.